HUBUNGAN ANTARA PERSEN PENUTUPAN SALVINIA MOLESTA DAN PERTUMBUHAN IKAN NILA (TILAPIA NILOTICA) - YUN INDIARTO (BERITA BIOLOGI, 1988)
YUN INDIARTO.1988,Relationship between percent coverage of Salvinia molesta f nd growth rate of Nile Tilapia (Tilapia nilotica),Berita Biologi 3(8) : 400 - 404.A study on the growth rate of Nile Tilapia in relation to various coverage of S.molesta has been conducted in experimental ponds for twelve weeks. Anaiysis of variance shows that the percent coverage of S.molesta affected significantly the growth rate of the Nile Tilapia (weight : F>F 0.01 and length : F > F0.05).It was found that 50% coverage or more may reduce the tish growth rate.The best growth rate was 1 reached at 25% coverage.Environmental condition:related to the above findings are discussed.